Repurposing anti-inflammatory drugs for fighting planktonic and biofilm growth. New carbazole derivatives based on the NSAID carprofen: synthesis, in silico and in vitro bioevaluation - Dumitrascu, Florea; Caira, Mino R.; Avram, Speranta; Buiu, Catalin; Udrea, Ana Maria; Vlad, Ilinca Margareta; Zarafu, Irina; Ioniță, Petre; Nuță, Diana Camelia; Popa, Marcela; Chifiriuc, Mariana-Carmen; Limban, Carmen (Frontiers in Cellular and Infection Microbiology, 2023)
One of the promising leads for the rapid discovery of alternative antimicrobial agents is to repurpose other drugs, such as nonsteroidal anti-inflammatory agents (NSAIDs) for fighting bacterial infections and antimicrobial resistance. A series of new carbazole derivatives based on the readily available anti-inflammatory drug carprofen has been obtained by nitration, halogenation and N-alkylation of carprofen and its esters. The structures of these carbazole compounds were assigned by NMR and IR spectroscopy. Regioselective electrophilic substitution by nitration and halogenation at the carbazole ring was assigned from H NMR spectra. The single crystal X-ray structures of two representative derivatives obtained by dibromination of carprofen, namely 3,8-dibromocarprofen and its methyl ester, were also determined, revealing significant differences in their supramolecular assemblies. The total antioxidant capacity (TAC) was measured using the DPPH method, the most active compound being 1i, bearing one chlorine and two bromine atoms, as well as the CO2Me group. The antimicrobial activity assay was performed using quantitative methods, allowing establishment of the minimal inhibitory/bactericidal/biofilm eradication concentrations (MIC.MBC/MBEC) on Gram-positive (Staphylococcus aureus, Enterococcus faecalis) and Gram-negative (Escherichia coli, Pseudomonas aeruginosa) strains. Among the tested derivatives, 1h bearing one chlorine and two bromine atoms has exhibited the widest antibacterial spectrum and the most intensive inhibitory activity, especially against the Gram-positive strains, in planktonic and biofilm growth state. The compound 1a (bearing one chlorine, one NO2 and one CO2Me group) and 1i (bearing one chlorine, two bromine atoms and a CO2Me group) exhibited the best antibiofilm activity in the case of the P. aeruginosa strain. Moreover, these compounds comply with the drug-likeness rules, have good oral bioavailability and are not carcinogenic or mutagenic. The results demonstrate that these new carbazole derivatives have a molecular profile which deserves to be explored further for the development of novel antibacterial and antibiofilm agents.